Depositional slope surface of the western margin of the Nylsvlei, South Africa : active piedmont aggradation and sedimentation processes. - Burri, Nicole M. (My University, 2014)
The Nyl River and its floodplain are situated on the eastern foothills of the Waterberg mountain range in the Limpopo Province of South Africa. Tributaries flowing out of the Waterberg range display unusual downstream changes, as they approach and converge with the Nylsvlei (or Nyl floodplain). Tributary channels decrease in size downstream until, eventually, they disappear altogether forming unchannellized floodouts. On one such floodout, on the farm Driefontein, an actively aggrading piedmont has formed adjacent to the famous Wonderkrater peat mound, known for its pollen record dating back ~45,000 years. Sediments from the aggrading piedmont interlace with Wonderkrater’s peat layers, suggesting that as the piedmont aggrades so too does the peat mound. This setting presents a unique opportunity to study active aggradational processes, and their products, on hillslope deposits and floodout environments. This study aims to describe the geomorphology and nature of depositional processes along the length of the piedmont adjacent to the Wonderkrater peat mound. Cross-sections, drainage channels and vegetation indices based on topographic maps, orthophotographs and hyperspectral images, were created using ArcGIS in order to describe and determine the surface morphology and hydrology of the Driefontein piedmont in detail. Surface soil samples were collected in order to determine particle size distribution, which were in turn compared to vegetation indices and changes in slope elevation. Further grain samples were collected from depth for age dating using Optically Stimulated Luminescence (OSL), as well as to determine grain size distribution in relation to surface sediments and other fluvial environments. Hyperspectral indices were found to correlate to surface grain size distribution, demonstrating that the presence of vegetation acts as a retaining mechanism for particles along hillslopes where incline should be too steep to support fine-grained sedimentary material. Surface sediments were found to demonstrate the characteristics of an alluvial floodout system, affected greatly by the presence of vegetation and slope inclination. Sub-surface samples were characteristic of a colluvial setting, suggesting that pediment retreat and basin fill, coupled with evidential climatic changes, were dominant controls on the pediment’s morphological and aggradational mechanisms. OSL age results estimated the sediments to be between 37.33 and 58.66 ka old. As a result of its unique sedimentary characteristics, a new type of ‘slow creep fan’ class was established in order to describe the characteristics of the Driefontein piedmont.
Keywords: Sediments (Geology); Floodplains - South Africa - Nyl River.; Nyl River (South Africa)